Fish Assemblages Associated with Natural and Anthropogenically-Modified Habitats in a Marine Embayment: Comparison of Baited Videos and Opera-House Traps - Wakefield, Corey; Lewis, P.; Coutts, T.; Fairclough, D.; Langlois, T. (Public Library of Science, 2013)
Marine embayments and estuaries play an important role in the ecology and life history of many fish species. Cockburn Sound is one of a relative paucity of marine embayments on the west coast of Australia. Its sheltered waters and close proximity to a capital city have resulted in anthropogenic intrusion and extensive seascape modification. This study aimed to compare the sampling efficiencies of baited videos and fish traps in determining the relative abundance and diversity of temperate demersal fish species associated with naturally occurring (seagrass, limestone outcrops and soft sediment) and modified (rockwall and dredge channel) habitats in Cockburn Sound. Baited videos sampled a greater range of species in higher total and mean abundances than fish traps. This larger amount of data collected by baited videos allowed for greater discrimination of fish assemblages between habitats. The markedly higher diversity and abundances of fish associated with seagrass and limestone outcrops, and the fact that these habitats are very limited within Cockburn Sound, suggests they play an important role in the fish ecology of this embayment. Fish assemblages associated with modified habitats comprised a subset of species in lower abundances when compared to natural habitats with similar physical characteristics. This suggests modified habitats may not have provided the necessary resource requirements (e.g. shelter and/or diet) for some species, resulting in alterations to the natural trophic structure and interspecific interactions.Baited videos provided a more efficient and non-extractive method for comparing fish assemblages and habitat associations of smaller bodied species and juveniles in a turbid environment.